2012
DOI: 10.1038/nrc3379
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase signalling networks in cancer

Abstract: Phospholipases (PLC, PLD and PLA) are essential mediators of intracellular and intercellular signalling. They can function as phospholipid-hydrolysing enzymes that can generate many bioactive lipid mediators, such as diacylglycerol, phosphatidic acid, lysophosphatidic acid and arachidonic acid. Lipid mediators generated by phospholipases regulate multiple cellular processes that can promote tumorigenesis, including proliferation, migration, invasion and angiogenesis. Although many individual phospholipases hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
163
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(167 citation statements)
references
References 136 publications
2
163
1
1
Order By: Relevance
“…Recently, Campos et al (69) reported that hBMSCs stimulated by proinflammatory cytokines had enhanced levels of 20:4n-6-containing PC species 38:4. The 20:4n-6 signaling also has a pronounced role in tumor cells, which have high expression levels of PLA 2 s and COX-2, and enhanced production of PGE2 (70,71). Differentiation-related increase of GPL species with 20:4n-6 was recently found in cultured neural stem cells (72).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Campos et al (69) reported that hBMSCs stimulated by proinflammatory cytokines had enhanced levels of 20:4n-6-containing PC species 38:4. The 20:4n-6 signaling also has a pronounced role in tumor cells, which have high expression levels of PLA 2 s and COX-2, and enhanced production of PGE2 (70,71). Differentiation-related increase of GPL species with 20:4n-6 was recently found in cultured neural stem cells (72).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these data support a role of Pla2g16 in tumorigenesis in vivo. Although Pla2g16-null mice or mice with mutations in other phospholipases are not cancer-prone, many of these mice decrease tumor progression when combined with other oncogenic defects (49). Crosses of Pla2g16 mice with p53 mutant mice will be invaluable in deciphering the in vivo role of Pla2g16 in metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have concluded that PLD2 is critically linked to the signals that mediate the processes involved tumorigenesis (transformation and tumor growth) and metastasis (Park et al, 2012). SOS, which activates the Ras-MAPK cascade, can be recruited to the plasma membrane by PLD2-derived PA generation, and eventually, MAPK signaling increases cell proliferation and transformation in NIH-3T3 cells (Zhao et al, 2007).…”
Section: Notementioning
confidence: 99%
“…PLD2 can be activated by multiple extracellular ligands and the major roles of PLD2 can be achieved by PA generation. PA is considered as a second messenger that mediates a variety of cellular functions such as, proliferation, cell growth, vesicle trafficking (endocytosis and exocytosis), and actin-cytoskeletal arrangement (Park et al, 2012). Furthermore, animal studies have shown that PLD2 can serve as a key mediator of in vivo pathophysiologic functions (Oliveira et al, 2010).…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation